Zustandsüberwachung zur Prognose der Restlebensdauer von Gummi-Metall-Elementen unter Berücksichtigung systembasierter Unsicherheiten - Bender, Amelie
Eine zustandsbasierte Instandhaltungsstrategie reduziert das Risiko eines Ausfalls eines technischen Systems bei gleichzeitig hoher Ausnutzung und planbaren Instandhaltungsmaßnahmen. Das Ziel dieser Arbeit liegt in der Entwicklung einer Zustandsüberwachung für Gummi-Metall-Elemente. Die Herausforderungen dieser Zustandsüberwachung leiten sich aus dem viskoelastischen Verhalten sowie dem komplexen Degradationsverhalten der Elemente ab. Infolge der daraus resultierenden Unsicherheiten werden die Elemente heutzutage präventiv instandgehalten. In Lebensdauerversuchen der Gummi-Metall-Elemente werden drei Messgrößen detektiert. Dabei wird mit der Temperatur eine Messgröße identifiziert, die am geeignetsten zur Beschreibung des Zustands der Elemente ist. Generell wird die Genauigkeit einer Zustandsüberwachung durch verschiedene Unsicherheiten beeinflusst. Für die Prognose der nutzbaren Restlebensdauer der Gummi-Metall-Elemente wird das Partikelfilter, eine verbreitete modellbasierte Methode zur Zustandsüberwachung technischer Systeme, weiterentwickelt, um Unsicherheiten im Verhalten und der Degradation der Elemente zu berücksichtigen. Anhand der Ergebnisse wird belegt, dass aufbauend auf dieser Zustandsüberwachung die Ausnutzung der Gummi-Metall-Elemente in realen Anwendungen durch eine präventive Instandhaltung erhöht werden kann. Damit bildet diese Arbeit die Basis für zukünftige, prädiktive Instandhaltungskonzepte für diese Elemente. Weiterhin bestätigt die Arbeit, dass eine Berücksichtigung vorliegender Unsicherheiten zu einem frühen Zeitpunkt im Entwicklungsprozess des Zustandsüberwachungssystems empfehlenswert ist.
Keywords: Zustandsüberwachung; Prognose der Restlebensdauer; modellbasierte Prognose; Partikelfilter; Unsicherheiten; Gummi; Verlässlichkeit; Lebensdauerversuche; Predictive Maintenance

FLight: FPGA Acceleration of Lightweight DNN Model Inference in Industrial Analytics - Ghasemzadeh Mohammadi, Hassan; Jentzsch, Felix; Kuschel, Maurice; Arshad, Rahil; Rautmare, Sneha; Manjunatha, Suraj; Platzner, Marco; Boschmann, Alexander; Schollbach, Dirk (Machine Learning and Principles and Practice of Knowledge Discovery in Databases)

Neural Correlates of Augmented Feedback Processing are Associated to Short-Term Behavioral Changes and Automaticity in Motor Learning - Krause, Daniel; Margraf, Linda; Weigelt, Matthias

Predictive value of valence-dependent neural correlates of augmented feedback processing for behavioral adaptation and learning in extensive motor learning - Krause, Daniel; Margraf, Linda; Weigelt, Matthias

Neural Processing of Augmented Feedback is Valence-Dependent and Changes After Extensive Practice of a New Motor Task - Margraf, Linda; Krause, Daniel; Weigelt, Matthias

Changes in valence-dependent neural correlates of augmented feedback processing after extensive motor sequence learning - Margraf, Linda; Krause, Daniel; Weigelt, Matthias

Effects of an Intervention for Promoting Basic Motor Competencies in Middle Childhood - Strotmeyer, Anne; Kehne, Miriam; Herrmann, Christian (International Journal of Environmental Research and Public Health)
The development of motor competencies is necessary for participation in the culture of sport, exercise, and physical activity, which in turn supports the development of a healthy lifestyle. A lack of physical activity in childhood and deficits in motor performance emphasize the relevance of interventions for promoting basic motor competencies. However, there are research desiderata with regard to such interventions. This article describes an intervention program for promoting basic motor competencies in middle childhood (around 6 to 10 years of age). The intervention was investigated in a longitudinal study from June 2019 to January 2020 (n = 200; 58% girls, M = 8.84 years, SD = 0.63) at three primary schools. The intervention was conducted once a week in physical education (PE). The comparison group participated in regular PE. The intervention showed significant effects on basic motor competencies in object movement but not in self-movement. The results demonstrate that positive effects on basic motor competencies can be achieved with the help of a relatively simple intervention. Further longitudinal studies are desirable as a means of substantiating the results and developing evidence-based concepts to support children in their development in the best possible way.
Keywords: Health; Toxicology and Mutagenesis; Public Health; Environmental and Occupational Health

Repeating head fakes in basketball: Temporal aspects affect the congruency-sequence effect - Polzien, A.; Güldenpenning, Iris; Weigelt, Matthias (Abstracts of the 63rd Conference of Experimental Psychologists (TeaP))

Cognitive load reduces interference by head fakes in basketball - Güldenpenning, Iris; Kunde, W.; Weigelt, Matthias (Abstracts of the 63rd Conference of Experimental Psychologists (TeaP))

Der Einfluss von Kontextinformationen auf den Blicktäuschungseffekt im Basketball - Güldenpenning, Iris; Barkey, Thies; Jackson, Robin C.; Weigelt, Matthias (Talententwicklung und Coaching im Sport. Abstractband der 53. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))

A multirate variational approach to Nonlinear MPC - Lishkova, Y.; Cannon, M.; Ober-Blöbaum, Sina

Co-simulation of MATLAB and ANSYS for ultrasonic wire bonding process optimization - Schemmel, Reinhard; Krieger, Viktor; Hemsel, Tobias; Sextro, Walter (Microelectronics Reliability)
Ultrasonic wire bonding is a solid-state joining process, used in the electronics industry to form electrical connections, e.g. to connect electrical terminals within semiconductor modules. Many process parameters affect the bond strength, such like the bond normal force, ultrasonic power, wire material and bonding frequency. Today, process design, development, and optimization is most likely based on the knowledge of process engineers and is mainly performed by experimental testing. In this contribution, a newly developed simulation tool is presented, to reduce time and costs and efficiently determine optimized process parameter. Based on a co-simulation of MATLAB and ANSYS, the different physical phenomena of the wire bonding process are considered using finite element simulation for the complex plastic deformation of the wire and reduced order models for the transient dynamics of the transducer, wire, substrate and bond formation. The model parameters such as the coefficients of friction between bond tool and wire and between wire and substrate were determined for aluminium and copper wire in experiments with a test rig specially developed for the requirements of heavy wire bonding. To reduce simulation time, for the finite element simulation a restart analysis and high performance computing is utilized. Detailed analysis of the bond formation showed, that the normal pressure distribution in the contact between wire and substrate has high impact on bond formation and distribution of welded areas in the contact area.
Keywords: Ultrasonic heavy wire bonding; Co-simulation; ANSYS; MATLAB; Process optimization; Friction coefficient; Copper-copper; Aluminium-copper

Hybrid Prediction Method for Remaining Useful Lifetime Estimation Considering Uncertainties - Bender, Amelie; Sextro, Walter (Proceedings of the European Conference of the PHM Society 2021)
Predictive Maintenance as a desirable maintenance strategy in industrial applications relies on suitable condition monitoring solutions to reduce costs and risks of the monitored technical systems. In general, those solutions utilize model-based or data-driven methods to diagnose the current state or predict future states of monitored technical systems. However, both methods have their advantages and drawbacks. Combining both methods can improve uncertainty consideration and accuracy. Different combination approaches of those hybrid methods exist to exploit synergy effects. The choice of an appropriate approach depends on different requirements and the goal behind the selection of a hybrid approach. In this work, the hybrid approach for estimating remaining useful lifetime takes potential uncertainties into account. Therefore, a data-driven estimation of new measurements is integrated within a model-based method. To consider uncertainties within the system, a differentiation between different system behavior is realized throughout diverse states of degradation. The developed hybrid prediction approach bases on a particle filtering method combined with a machine learning method, to estimate the remaining useful lifetime of technical systems. Particle filtering as a Monte Carlo simulation technique is suitable to map and propagate uncertainties. Moreover, it is a state-of-the-art model-based method for predicting remaining useful lifetime of technical systems. To integrate uncertainties a multi-model particle filtering approach is employed. In general, resampling as a part of the particle filtering approach has the potential to lead to an accurate prediction. However, in the case where no future measurements are available, it may increase the uncertainty of the prediction. By estimating new measurements, those uncertainties are reduced within the data-driven part of the approach. Hence, both parts of the hybrid approach strive to account for and reduce uncertainties. Rubber-metal-elements are employed as a use-case to evaluate the developed approach. Rubber-metal-elements, which are used to isolate vibrations in various systems, such as railways, trucks and wind turbines, show various uncertainties in their behavior and their degradation. Those uncertainties are caused by diverse inner and outer factors, such as manufacturing influences and operating conditions. By expert knowledge the influences are described, analyzed and if possible reduced. However, the remaining uncertainties are considered within the hybrid prediction method. Relative temperature is the selected measurand to describe the element’s degradation. In lifetime tests, it is measured as the difference between the element’s temperature and the ambient temperature. Thereby, the influence of the ambient temperature on the element’s temperature is taken into account. Those elements show three typical states of degradation that are identified within the temperature measurements. Depending on the particular state of degradation a new measurement is estimated within the hybrid approach to reduce potential uncertainties. Finally, the performance of the developed hybrid method is compared to a model-based method for estimating the remaining useful lifetime of the same elements. Suitable performance indices are implemented to underline the differences between the results.
Keywords: Hybrid prediction method; Multi-model particle filtering; Uncertainty quantification; RUL estimation

On the applicability of time series features as health indicators for technical systems operating under varying conditions - Aimiyekagbon, Osarenren Kennedy; Bender, Amelie; Sextro, Walter (Proceedings of the Seventeenth International Conference on Condition Monitoring and Asset Management (CM 2021))
Several methods, including order analysis, wavelet analysis and empirical mode decomposition have been proposed and successfully employed for the health state estimation of technical systems operating under varying conditions. However, where information such as the speed of rotating machinery, component specifications or other domain-specific information is unavailable, such methods are often infeasible. Thus, this paper investigates the application of classical time-domain features, features from the medical field and novel features from the highly comparative time-series analysis (HCTSA) package, for the health state estimation of rotating machinery operating under varying conditions. Furthermore, several feature selection methods are investigated to identify features as viable health indicators for the diagnostics and prognostics of technical systems. As a case study, the presented methods are evaluated on real-world and experimentally acquired vibration data of bearings operating under varying speed. The results show that the selected features can successfully be employed as health indicators for technical systems operating under varying conditions.
Keywords: Wind turbine diagnostics; bearing diagnostics; non-stationary operating conditions; varying operating conditions; feature extraction; feature selection; fault detection; failure detection

Rule-based Diagnostics of a Production Line - Aimiyekagbon, Osarenren Kennedy; Muth, Lars; Wohlleben, Meike Claudia; Bender, Amelie; Sextro, Walter (Proceedings of the European Conference of the PHM Society 2021)
In the industry 4.0 era, there is a growing need to transform unstructured data acquired by a multitude of sources into information and subsequently into knowledge to improve the quality of manufactured products, to boost production, for predictive maintenance, etc. Data-driven approaches, such as machine learning techniques, are typically employed to model the underlying relationship from data. However, an increase in model accuracy with state-of-the-art methods, such as deep convolutional neural networks, results in less interpretability and transparency. Due to the ease of implementation, interpretation and transparency to both domain experts and non-experts, a rule-based method is proposed in this paper, for prognostics and health management (PHM) and specifically for diagnostics. The proposed method utilizes the most relevant sensor signals acquired via feature extraction and selection techniques and expert knowledge. As a case study, the presented method is evaluated on data from a real-world quality control set-up provided by the European prognostics and health management society (PHME) at the conference’s 2021 data challenge. With the proposed method, our team took the third place, capable of successfully diagnosing different fault modes, irrespective of varying conditions.
Keywords: PHME 2021; Feature Selection Classification; Feature Selection Clustering; Interpretable Model; Transparent Model; Industry 4.0; Real-World Diagnostics; Quality Control; Predictive Maintenance

Anomaly detection in hot forming processes using hybrid modeling - Lenz, Cederic; Henke, Christian; Trächtler, Ansgar (2021 26th IEEE International Conference on Emerging Technologies and Factory Automation (ETFA))

Efficient semi-analytical simulation of elastic guided waves in cylinders subject to arbitrary non-symmetric loads - Itner, Dominik; Gravenkamp, Hauke; Dreiling, Dmitrij; Feldmann, Nadine; Henning, Bernd (Ultrasonics)

HighPerMeshes – A Domain-Specific Language for Numerical Algorithms on Unstructured Grids - Alhaddad, Samer; Förstner, Jens; Groth, Stefan; Grünewald, Daniel; Grynko, Yevgen; Hannig, Frank; Kenter, Tobias; Pfreundt, Franz-Josef; Plessl, Christian; Schotte, Merlind; Steinke, Thomas; Teich, Jürgen; et al. (Euro-Par 2020: Parallel Processing Workshops)
Solving partial differential equations on unstructured grids is a cornerstone of engineering and scientific computing. Nowadays, heterogeneous parallel platforms with CPUs, GPUs, and FPGAs enable energy-efficient and computationally demanding simulations. We developed the HighPerMeshes C++-embedded Domain-Specific Language (DSL) for bridging the abstraction gap between the mathematical and algorithmic formulation of mesh-based algorithms for PDE problems on the one hand and an increasing number of heterogeneous platforms with their different parallel programming and runtime models on the other hand. Thus, the HighPerMeshes DSL aims at higher productivity in the code development process for multiple target platforms. We introduce the concepts as well as the basic structure of the HighPerMeshes DSL, and demonstrate its usage with three examples, a Poisson and monodomain problem, respectively, solved by the continuous finite element method, and the discontinuous Galerkin method for Maxwell’s equation. The mapping of the abstract algorithmic description onto parallel hardware, including distributed memory compute clusters, is presented. Finally, the achievable performance and scalability are demonstrated for a typical example problem on a multi-core CPU cluster.
Keywords: tet_topic_hpc

Evaluating the Design Space for Offloading 3D FFT Calculations to an FPGA for High-Performance Computing - Ramaswami, Arjun; Kenter, Tobias; Kühne, Thomas; Plessl, Christian (Applied Reconfigurable Computing. Architectures, Tools, and Applications)

The HighPerMeshes framework for numerical algorithms on unstructured grids - Alhaddad, Samer; Förstner, Jens; Groth, Stefan; Grünewald, Daniel; Grynko, Yevgen; Hannig, Frank; Kenter, Tobias; Pfreundt, Franz‐Josef; Plessl, Christian; Schotte, Merlind; Steinke, Thomas; Teich, Jürgen; et al. (Concurrency and Computation: Practice and Experience)
Keywords: tet_topic_hpc

Optical PRBS Generation with Threefold Bandwidth of the Employed Electronics and Photonics - Singh, Karanveer; Meier, Janosch; Preussler, Stefan; Kress, Christian; Scheytt, J. Christoph; Schneider, Thomas (OSA Advanced Photonics Congress 2021)
We present the optical generation of a 300 Gbaud PRBS-7 data signal based on time-division multiplexing of Nyquist sinc-pulse sequences. The employed electronic and photonic components need only one-third of the final bandwidth.

Diffusion of the carbon dioxide–ethanol mixture in the extended critical region - Chatwell, René Spencer; Guevara-Carrion, Gabriela; Gaponenko, Yuri; Shevtsova, Valentina; Vrabec, Jadran (Physical Chemistry Chemical Physics)
The effect of traces of ethanol in supercritical carbon dioxide on the mixture's thermodynamic properties is studied by molecular simulations and Taylor dispersion measurements.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Andrea Karimé: Sterne im Kopf und ein unglaublicher Plan. Köln: Peter Hammer Verlag 2021 - Lammer, Christina

Nachhaltigkeitsmärkte im Vergleich. Zur Transformation von Staatlichkeit - Knoll, Lisa (Der Staat in der Großen Transformation)

Bewerten und Prüfen. Zur Relevanz der Figur der Prüfung für die Organisationssoziologie - Knoll, Lisa (Organisation und Bewertung)

Digitale Begleitseminare im Praxissemester der gewerblich-technischen Fachrichtungen - Jonas-Ahrend, Gabriela; Vernholz, Mats; Temmen, Katrin
In diesem Beitrag werden die Elemente „Begleitseminar“ und „Begleitforschungsseminar“ des Praxissemesters für Lehramtsstudierende der beruflichen Fachrichtungen Maschinenbautechnik und Elektrotechnik an der Universität Paderborn im Hinblick auf die Veränderungen durch die Covid-19-Pandemie erläutert.

Как попрощаться с роботом? Исследование достижения разговорного закрытия - Егорова, Анастасия Игоревна; Klowait, Nils (The monitoring of public opinion economic&social changes)
Разговорные компьютеризированные агенты совершенствуются, развиваются и получают все более широкое распространение в различных сферах жизни. Теперь искусственный интеллект может вести беседу с человеком, используя сложные разговорные приемы и человекоподобные речевые паттерны. Например, Google Duplex, современный голосовой интерфейс, способен автономно выполнять сервисные телефонные звонки таким образом, что собеседнику не удается опознать в нем робота. С увеличением числа интерактивных коммуникаций человека и компьютера становится очевидной необходимость их изучения: каким образом они происходят, как разрешаются недоразумения и достигаются цели разговора. Статья посвящена эмпирическому изучению взаимодействия между продвинутым разговорным агентом и человеком: в рамках этнометодологии и конверсационного анализа рассмотрены последовательно разворачивающиеся, естественно возникающие речевые практики собеседников, а также порождаемые ими нормативные структуры. Материалом для анализа послужила аудиозапись телефонной беседы между Google Duplex и человеком-оператором. Исследовано, в частности, как достигается разговорное закрытие — микроструктура, требующая кооперации собеседников в организации чередования реплик. Показано, что завершение беседы происходит за счет постепенного достижения эпистемического равновесия между говорящими, несмотря на интеракционные проблемы, возникающие из-за неуместного просодического контура робота. Подчеркивается связь между институциональным контекстом взаимодействия и роботизированной природой не-человеческого собеседника. Полученные результаты закладывают основу для дальнейших исследований специфического порядка во взаимодействии человека и робота и способствуют более глубокому пониманию того, как завершается разговор в пограничных случаях. Благодарности. Статья подготовлена в сотрудничестве с Лабораторией геймификации Сбербанка. Статья подготовлена в рамках гранта, предоставленного Министерством науки и высшего образования Российской Федерации (№ соглашения о предоставлении гранта: 075-15-2020-908).
Keywords: Economics; Econometrics and Finance (miscellaneous); Sociology and Political Science

Batterien als Medien häuslicher Mobilität: Materialitäten und kulturelle Imaginationen der Überwindung des Zuhauses - Miggelbrink, Monique (Reichweitenangst. Batterien und Akkus als Medien des Digitalen Zeitalters)

Home Computer: Wohnen mit dem Computer in Einrichtungszeitschriften - Miggelbrink, Monique (WohnSeiten. Visuelle Konstruktionen des Wohnens in Zeitschriften)

Big-M-small-N temporal-oder judgment data - Tünnermann, Jan; Scharlau, Ingrid (The Quantitative Methods of Psychology)

Home-Office - Figurationen häuslicher Arbeit - Miggelbrink, Monique; Bartz, Christina (Selbstbehältnisse. Orte und Gegenstände der Aufbewahrung von Individualität)

Die Gesellschaft im Werbebild. Werbung und das Wissen um Gesellschaft und Telekommunikation - Bartz, Christina (Bildforschung aus interdisziplinärer Perspektive)

Non-Invasive Visualization of Ferroelectric Domain Structures on the Non-Polar y-Surface of KTiOPO4 via Raman Imaging - Brockmeier, Julian; Mackwitz, Peter Walter Martin; Rüsing, Michael; Eigner, Christof; Padberg, Laura; Santandrea, Matteo; Silberhorn, Christine; Zrenner, Artur; Berth, Gerhard (Crystals)
Potassium titanyl phosphate (KTP) is a nonlinear optical material with applications in high-power frequency conversion or quasi-phase matching in submicron period domain grids. A prerequisite for these applications is a precise control and understanding of the poling mechanisms to enable the fabrication of high-grade domain grids. In contrast to the widely used material lithium niobate, the domain growth in KTP is less studied, because many standard methods, such as selective etching or polarization microscopy, provides less insight or are not applicable on non-polar surfaces, respectively. In this work, we present results of confocal Raman-spectroscopy of the ferroelectric domain structure in KTP. This analytical method allows for the visualization of domain grids of the non-polar KTP y-face and therefore more insight into the domain-growth and -structure in KTP, which can be used for improved domain fabrication.

Labor-Management Relations and Varieties of Capitalism - Schneider, Martin R. (Handbook of Labor, Human Resources and Population Economics)

Extremely low-energy ARPES of quantum well states in cubic-GaN/AlN and GaAs/AlGaAs heterostructures - Hajlaoui, Mahdi; Ponzoni, Stefano; Deppe, Michael; Henksmeier, Tobias; As, Donat Josef; Reuter, Dirk; Zentgraf, Thomas; Springholz, Gunther; Schneider, Claus Michael; Cramm, Stefan; Cinchetti, Mirko (Scientific Reports)
Abstract Quantum well (QW) heterostructures have been extensively used for the realization of a wide range of optical and electronic devices. Exploiting their potential for further improvement and development requires a fundamental understanding of their electronic structure. So far, the most commonly used experimental techniques for this purpose have been all-optical spectroscopy methods that, however, are generally averaging in momentum space. Additional information can be gained by angle-resolved photoelectron spectroscopy (ARPES), which measures the electronic structure with momentum resolution. Here we report on the use of extremely low-energy ARPES (photon energy ~ 7 eV) to increase depth sensitivity and access buried QW states, located at 3 nm and 6 nm below the surface of cubic-GaN/AlN and GaAs/AlGaAs heterostructures, respectively. We find that the QW states in cubic-GaN/AlN can indeed be observed, but not their energy dispersion, because of the high surface roughness. The GaAs/AlGaAs QW states, on the other hand, are buried too deep to be detected by extremely low-energy ARPES. Since the sample surface is much flatter, the ARPES spectra of the GaAs/AlGaAs show distinct features in momentum space, which can be reconducted to the band structure of the topmost surface layer of the QW structure. Our results provide important information about the samples’ properties required to perform extremely low-energy ARPES experiments on electronic states buried in semiconductor heterostructures.

The ‚teachwodd training concept’ a contribution to the implementation of practical technological learning in primary schools. - Tenberge, Claudia; Gödiker, Manon

Load Data Acquisition in Rural East Africa for the Layout of Microgrids and Demand–Side–Management Measures - Kakande, Josephine Nakato; Philipo, Godiana Hagile; Krauter, Stefan (Proceedings of the 38th European Photovoltaic Solar Energy Conference and Exhibition (EUPVSEC 2021))
With its growing population and industrialization, DREs, and solar technologies in particular, provide a sustainable means of bridging the current energy deficit in Africa, increasing supply reliability and meeting future demand. Data acquisition and data management systems allow real time monitoring and control of energy systems as well as performance analysis. However commercial data acquisition systems often have cost implications that are prohibitive for small PV systems and installations in developing countries. In this paper, a multi-user, multi-purpose microgrid database system is designed and implemented. MAVOWATT 270 power quality analyzers by GOSSEN METRAWATT, raspberry pi modules and sensors are used for measuring, recording and storing electrical and meteorological data in East Africa. Socio-economic data is also stored in the database. The designed system employs open source software and hardware solutions which are best suited to developing regions like East Africa due to the lower cost implications. The expected results promise a comprehensive database covering different electro-technical and socio-economic parameters useful for optimal design of microgrid systems.
Keywords: Art-D; Afrika; Demand side management; MySQL; Raspberry pi; Data acquisition

Diagnosen (h)erstellen – Sprachwissenschaftliche Zugänge - Felder, Ekkehard; Schuster, Britt-Marie; Spranz-Fogasy, Thomas (Linguistik und Medizin)
Keywords: Fachkommunikation

Widersprechen als diskursive Praktik. Illustriert an der Widerstandskommunikation gegen den Nationalsozialismus (1933–1945) - Schuster, Britt-Marie (Protest, Protestieren, Protestkommunikation)
Keywords: Kommunikationsgeschichte

Bedeutungsvarianz und sozialer Stil - Schuster, Britt-Marie; Wilk, Nicole M. (Sprache des Sterbens – Sprache des Todes. Linguistische und interdisziplinäre Perspektivierungen eines zentralen Aspekts menschlichen Daseins)
Keywords: Textsemantik

Peeking beyond peaks: Challenges and research potentials of continuous multimodal multi-objective optimization - Grimme, Christian; Kerschke, Pascal; Aspar, Pelin; Trautmann, Heike; Preuss, Mike; Deutz, André H.; Wang, Hao; Emmerich, Michael (Computers & Operations Research)
Multi-objective (MO) optimization, i.e., the simultaneous optimization of multiple conflicting objectives, is gaining more and more attention in various research areas, such as evolutionary computation, machine learning (e.g., (hyper-)parameter optimization), or logistics (e.g., vehicle routing). Many works in this domain mention the structural problem property of multimodality as a challenge from two classical perspectives: (1) finding all globally optimal solution sets, and (2) avoiding to get trapped in local optima. Interestingly, these streams seem to transfer many traditional concepts of single-objective (SO) optimization into claims, assumptions, or even terminology regarding the MO domain, but mostly neglect the understanding of the structural properties as well as the algorithmic search behavior on a problem’s landscape. However, some recent works counteract this trend, by investigating the fundamentals and characteristics of MO problems using new visualization techniques and gaining surprising insights. Using these visual insights, this work proposes a step towards a unified terminology to capture multimodality and locality in a broader way than it is usually done. This enables us to investigate current research activities in multimodal continuous MO optimization and to highlight new implications and promising research directions for the design of benchmark suites, the discovery of MO landscape features, the development of new MO (or even SO) optimization algorithms, and performance indicators. For all these topics, we provide a review of ideas and methods but also an outlook on future challenges, research potential and perspectives that result from recent developments.
Keywords: Multimodal optimization; Multi-objective continuous optimization; Landscape analysis; Visualization; Benchmarking; Theory; Algorithms

On the Potential of Normalized TSP Features for Automated Algorithm Selection - Heins, Jonathan; Bossek, Jakob; Pohl, Janina; Seiler, Moritz; Trautmann, Heike; Kerschke, Pascal (Proceedings of the 16$^th$ ACM/SIGEVO Conference on Foundations of genetic Algorithms (FOGA XVI))
Classic automated algorithm selection (AS) for (combinatorial) optimization problems heavily relies on so-called instance features, i.e., numerical characteristics of the problem at hand ideally extracted with computationally low-demanding routines. For the traveling salesperson problem (TSP) a plethora of features have been suggested. Most of these features are, if at all, only normalized imprecisely raising the issue of feature values being strongly affected by the instance size. Such artifacts may have detrimental effects on algorithm selection models. We propose a normalization for two feature groups which stood out in multiple AS studies on the TSP: (a) features based on a minimum spanning tree (MST) and (b) a k-nearest neighbor graph (NNG) transformation of the input instance. To this end we theoretically derive minimum and maximum values for properties of MSTs and k-NNGs of Euclidean graphs. We analyze the differences in feature space between normalized versions of these features and their unnormalized counterparts. Our empirical investigations on various TSP benchmark sets point out that the feature scaling succeeds in eliminating the effect of the instance size. Eventually, a proof-of-concept AS-study shows promising results: models trained with normalized features tend to outperform those trained with the respective vanilla features.

Multi^3: Optimizing Multimodal Single-Objective Continuous Problems in the Multi-Objective Space by Means of Multiobjectivization - Aspar, Pelin; Kerschke, Pascal; Steinhoff, Vera; Trautmann, Heike; Grimme, Christian (Evolutionary Multi-Criterion Optimization: 11$^th$ International Conference, EMO 2021, Shenzhen, China, March 28–31, 2021, Proceedings)
In this work we examine the inner mechanisms of the recently developed sophisticated local search procedure SOMOGSA. This method solves multimodal single-objective continuous optimization problems by first expanding the problem with an additional objective (e.g., a sphere function) to the bi-objective space, and subsequently exploiting local structures and ridges of the resulting landscapes. Our study particularly focusses on the sensitivity of this multiobjectivization approach w.r.t. (i) the parametrization of the artificial second objective, as well as (ii) the position of the initial starting points in the search space. As SOMOGSA is a modular framework for encapsulating local search, we integrate Gradient and Nelder-Mead local search (as optimizers in the respective module) and compare the performance of the resulting hybrid local search to their original single-objective counterparts. We show that the SOMOGSA framework can significantly boost local search by multiobjectivization. Combined with more sophisticated local search and metaheuristics this may help in solving highly multimodal optimization problems in future.

What Is It About Humanity That We Can’t Give Away To Intelligent Machines? A European Perspective - Coombs, Crispin; Stacey, Patrick; Kawalek, Peter; Simeonova, Boyka; Becker, Jörg; Bergener, Katrin; Carvalho, João Álvaro; Fantinato, Marcelo; Garmann-Johnsen, Niels F.; Grimme, Christian; Stein, Armin; Trautmann, Heike (International Journal of Information Management)
One of the most significant recent technological developments concerns the development and implementation of ‘intelligent machines’ that draw on recent advances in artificial intelligence (AI) and robotics. However, there are growing tensions between human freedoms and machine controls. This article reports the findings of a workshop that investigated the application of the principles of human freedom throughout intelligent machine development and use. Forty IS researchers from ten different countries discussed four contemporary AI and humanity issues and the most relevant IS domain challenges. This article summarizes their experiences and opinions regarding four AI and humanity themes: Crime & conflict, Jobs, Attention, and Wellbeing. The outcomes of the workshop discussions identify three attributes of humanity that need preservation: a critique of the design and application of AI, and the intelligent machines it can create; human involvement in the loop of intelligent machine decision-making processes; and the ability to interpret and explain intelligent machine decision-making processes. The article provides an agenda for future AI and humanity research.

Towards Feature-Free Automated Algorithm Selection for Single-Objective Continuous Black-Box Optimization - Prager, Raphael Patrick; Vinzent Seiler, Moritz; Trautmann, Heike; Kerschke, Pascal (2021 IEEE Symposium Series on Computational Intelligence (SSCI))
We propose a novel method for automated algorithm selection in the domain of single-objective continuous black-box optimization. In contrast to existing methods, we use convolutional neural networks as the selection apparatus which bases its decision on a so-called ‘fitness map’. This fitness map is a 2D representation of a two dimensional search space where different gray scales indicate the quality of found solutions in certain areas. Our devised approach uses a modular CMA-ES framework which offers the option to create the conventional CMA-ES, CMA-ES with the alternate step-size adaptation and many other variants proposed over the years. In total, 4 608 different configurations are possible where most configurations are of complementary nature. In this proof-of-concept work, we consider a subset of 32 possible configurations. The developed method is evaluated against an excerpt of BBOB functions and its performance is compared against baselines that are commonly used in automated algorithm selection - the best standalone algorithm (configuration) and the best obtainable sequence of configurations. While the results indicate that the use of the fitness map is not superior on every benchmark problem, it indubitably shows its merit on more hard-to-solve problems. This offers a promising perspective for generalizing to other types of optimization problems and problem domains.

RP-Mod & RP-Crowd: Moderator- and Crowd-Annotated German News Comment Datasets - Assenmacher, Dennis; Niemann, Marco; Müller, Kilian; Seiler, Moritz V.; Riehle, Dennis M.; Trautmann, Heike (Proceedings of the Neural Information Processing Systems Track on Datasets and Benchmarks 1 (NeurIPS Datasets and Benchmarks 2021))
Abuse and hate are penetrating social media and many comment sections of news media companies. These platform providers invest considerable efforts to mod- erate user-generated contributions to prevent losing readers who get appalled by inappropriate texts. This is further enforced by legislative actions, which make non-clearance of these comments a punishable action. While (semi-)automated solutions using Natural Language Processing and advanced Machine Learning techniques are getting increasingly sophisticated, the domain of abusive language detection still struggles as large non-English and well-curated datasets are scarce or not publicly available. With this work, we publish and analyse the largest annotated German abusive language comment datasets to date. In contrast to existing datasets, we achieve a high labelling standard by conducting a thorough crowd-based an- notation study that complements professional moderators’ decisions, which are also included in the dataset. We compare and cross-evaluate the performance of baseline algorithms and state-of-the-art transformer-based language models, which are fine-tuned on our datasets and an existing alternative, showing the usefulness for the community.

Gender and Authority – The Entanglement of Two Concepts in High Medieval Historiography - Foerster, Anne (Geschlecht macht Herrschaft – Interdisziplinäre Studien zu vormoderner Macht und Herrschaft / Gender Power Sovereignty – Interdisciplinary Studies on Premodern Power)

Die Witwenschaft kinderloser Königinnen im Hochmittelalter - Foerster, Anne (Kinderlosigkeit im Mittelalter)

Erklärvideos in der Sprachwissenschaft – Sprache-Bild-Bezüge und ihr Einfluss auf den Lernerfolg (die hochschullehre – Jahrgang 7-2021)

A Database for Research on Detection and Enhancement of Speech Transmitted over HF links - Heitkaemper, Jens; Schmalenstroeer, Joerg; Ion, Valentin; Haeb-Umbach, Reinhold (Speech Communication; 14th ITG-Symposium)

How entrepreneur’s leadership behavior and demographics shape applicant attraction to new ventures: the role of stereotypes - Hubner-Benz, Sylvia; Rudic, Biljana; Baum, Matthias (The International Journal of Human Resource Management)
Keywords: Management of Technology and Innovation; Organizational Behavior and Human Resource Management; Strategy and Management; Business and International Management; Industrial relations

An Asia-centric approach to team innovation: Cultural differences in exploration and exploitation behavior - Hubner-Benz, Sylvia; Frese, Michael; Song, Zhaoli; Tripathi, Neha; Kaschner, Tamara; Le Kong, Xing (Journal of Business Research)
Keywords: Marketing

Introduction - Jacob, Joachim; Süßmann, Johannes (The Reception of Antiquity in the Age of Enlightenment. English Edition ed. by Christina C. Harker. Translated by Duncan Alexander Smart)

Investigating students' processes of noticing and interpreting syntactic language features in word problem solving through eye-tracking - Dröse, Jennifer; Prediger, S.; Neugebauer, P.; Danhier, R. D.; Mertins, B. (International Electronic Journal of Mathematics Education, 16(1), em0625)

Identifying obstacles is not enough for everybody – Differential efficacy of an intervention fostering fifth graders’ comprehension for word problems - Dröse, Jennifer; Prediger, S. (Studies in Educational Evaluation, 68 (100953))

Prokrastination bei Studierenden verringern durch Anwendung eines Ratgebers im Gruppensetting - Korsmeier, Teresa; Bobe, Julia; Klingsieck, Katrin B. (Zeitschrift für Beratung und Studium)

"Welcome to Night Vale" und/mit Derrida: Lernen, mit den Gespenstern zu leben? - Spener, Anna Maria (Literatur und das Böse. Beiträge des 10. Studierendenkongress Komparatistik)

"Meine Trauer war (k)eine Krankheit"? Achronologisches Erzählen einer anhaltenden Trauerstörung in Olga Grjasnowas "Der Russe ist einer, der Birken liebt" - Spener, Anna Maria (Anafora. Zeitschrift für Literaturwissenschaft)

A longitudinal analysis of the reciprocal relationship between academic procrastination, study satisfaction, and dropout intentions in higher education - Scheunemann, Anne; Schnettler, Theresa; Bobe, Julia; Fries, Stefan; Grunschel, Carola (European Journal of Psychology of Education)
Abstract Student dropout is a multi-causal process. Different theoretical models on student dropout consider dysfunctional study behavior (e.g., academic procrastination) and low study satisfaction as possible determinants of students’ dropout intentions during their university studies. However, these models neglect contemporary conceptualizations that assume reverse relationships between dropout intentions and other determinants of the dropout process. Until now, empirical evidence on these assumptions is scant. The present three-wave longitudinal study explored the reciprocal relationships between academic procrastination, study satisfaction, and dropout intentions over one semester. To this end, we used data of N = 326 undergraduate students enrolled in mathematics and law. Our latent cross-lagged panel model replicated existing empirical cross-sectional findings between the variables (i.e., academic procrastination, study satisfaction, and dropout intentions). Regarding the longitudinal relations, as expected, the cross-lagged effects showed that higher dropout intentions significantly related to subsequent higher academic procrastination and lower study satisfaction. Unexpectedly, academic procrastination did not significantly relate to subsequent dropout intentions. Additionally, higher study satisfaction significantly associated with subsequent higher dropout intentions—possibly due to unfulfilled expectations. Further, higher study satisfaction significantly related to subsequent higher procrastination—possibly due to more confidence among satisfied students. Our results broaden the view on dropout intentions as part of the dynamic interplay of student dropout determinants and the need to refine dropout models’ assumptions accordingly. Practically, realistic expectations seem important to reduce dropout intentions. Further, student counselors should have a closer look at the reasons for academic procrastination to develop individual solutions for this dysfunctional behavior.
Keywords: Developmental and Educational Psychology; Education

Digitales Praxissemester - kann das überhaupt gut gehen? - Göddertz, Nina (Care Work in der gesellschaftlichen Transformation. Beschäftigung, Bildung, Fachdidaktik)
Marianne Friese/Rita Braches-Chyrek Einführung Marianne Friese Care Work im Spannungsfeld gesellschaftlicher Transformation. Systemische Widersprüche und Entwicklungsperspektiven Berufliche Bildung und Beschäftigungssysteme Denise Becka und Michaela Evans Wohlfahrtsproduktion und Care im digitalen Wandel: Perspektiven für Beruflichkeit in der Pflege Heidrun Herzberg und Peter Alheit Zur Akzeptanz des Konzepts „Community Nurse" im Land Brandenburg: Eine qualitative Vorstudie Karin Reiber, Jan Braun und Jutta Mohr Berufliche Bildung in der Domäne Pflege zwischen Anforderungen des Beschäftigungssystems und individueller berufsbiografischer Entwicklung Philipp Struck Entwicklungs- und Verbesserungsperspektiven für berufliche (Aus-)Bildungsprozesse im Gesundheitswesen Rita Braches-Chyrek Soziale Arbeit: Ausbildung und Beschäftigung Julia Kastrup und Alexandra Brutzer Hauswirtschaft in Zeiten von Corona - Ergebnisse einer Interviewstudie mit Hauswirtschaftlichen Fachkräften Akademische Bildung und Weiterbildung Anna Bobe, Anke Karber und Tobias Moock Theorie und Praxis in sozialpädagogischen Bildungsgängen - Erste Strukturierungsansätze vielfältiger Verhältnisse Manuela Liebig, Mirjam Chris und Annemarie Marx „Am Ball bleiben" - Sensibilisierung für aktuelle Herausforderungen der sozialpädagogischen Praxis durch Arbeitsanalysen im Lehramtsstudium für berufliche Schulen Anja Walter, Martin Fritzenwanker, Martin Karstädt Von Berufsfeldanalysen zum Unterricht - empirisches Material für die Bildungspraxis im Berufsfeld Gesundheit und Pflege nutzen Nina Göddertz „Digitales Praxissemester - kann das überhaupt gut gehen?" - Reflexionen von Lehramtsstudierenden vor und während des Praxissemesters in Zeiten der Covid-19-Pandemie Stephanie Spanu Systemrelevant(e) ausbilden. Berufliches Lehramt, Fachrichtung Sozialpädagogik und die berufliche Bildung: Der Fachkräftemangel als gesellschaftliche Aufgabe Julia Kastrup, Birgit Peuker, Marie Nölle-Krug und Simon Vollmer Gemeinsam innovativ! - Transformative Themenfelder in der lehramtsbezogenen Ausbildung der beruflichen Fachrichtung Ernährung- und Hauswirtschaft standortübergreifend lehren und lernen Ursula Walkenhorst, Annika Lara Schwarze Digitale Transformation in der Hochschullehre - Chancen und Grenzen für die Gesundheitsberufe Dana Bergmann und Astrid Seltrecht Weiterbildungsordnungsarbeit für Pflegeberufe Claudia Schepers, Johanna Krawietz und Jella Fuchs Kollegiale Beratung für die Kitteltasche
Keywords: Modernisierung personenbezogener Dienstleistungsberufe Aktueller Forschungsstand; Best Practice und Desiderata

A Comparison and Combination of Unsupervised Blind Source Separation Techniques - Boeddeker, Christoph; Rautenberg, Frederik; Haeb-Umbach, Reinhold (ITG Conference on Speech Communication)
Unsupervised blind source separation methods do not require a training phase and thus cannot suffer from a train-test mismatch, which is a common concern in neural network based source separation. The unsupervised techniques can be categorized in two classes, those building upon the sparsity of speech in the Short-Time Fourier transform domain and those exploiting non-Gaussianity or non-stationarity of the source signals. In this contribution, spatial mixture models which fall in the first category and independent vector analysis (IVA) as a representative of the second category are compared w.r.t. their separation performance and the performance of a downstream speech recognizer on a reverberant dataset of reasonable size. Furthermore, we introduce a serial concatenation of the two, where the result of the mixture model serves as initialization of IVA, which achieves significantly better WER performance than each algorithm individually and even approaches the performance of a much more complex neural network based technique.

Convolutive Transfer Function Invariant SDR Training Criteria for Multi-Channel Reverberant Speech Separation - Boeddeker, Christoph; Zhang, Wangyou; Nakatani, Tomohiro; Kinoshita, Keisuke; Ochiai, Tsubasa; Delcroix, Marc; Kamo, Naoyuki; Qian, Yanmin; Haeb-Umbach, Reinhold (ICASSP 2021 - 2021 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

Open Range Pitch Tracking for Carrier Frequency Difference Estimation from HF Transmitted Speech - Schmalenstroeer, Joerg; Heitkaemper, Jens; Ullmann, Joerg; Haeb-Umbach, Reinhold (29th European Signal Processing Conference (EUSIPCO))

Rezension von: Jörg van Norden, Thomas Must, Lars Deile, Peter Riedel, Susan Krause und Wanda Schürenberg (Hgg.): Geschichtsdidaktische Grundbegriffe. Ein Bilderbuch für Studium, Lehre und Beruf. Hannover 2020 - Hartung, Olaf (H-Soz-Kult)

Geometry calibration in wireless acoustic sensor networks utilizing DoA and distance information - Gburrek, Tobias; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (EURASIP Journal on Audio, Speech, and Music Processing)
Due to the ad hoc nature of wireless acoustic sensor networks, the position of the sensor nodes is typically unknown. This contribution proposes a technique to estimate the position and orientation of the sensor nodes from the recorded speech signals. The method assumes that a node comprises a microphone array with synchronously sampled microphones rather than a single microphone, but does not require the sampling clocks of the nodes to be synchronized. From the observed audio signals, the distances between the acoustic sources and arrays, as well as the directions of arrival, are estimated. They serve as input to a non-linear least squares problem, from which both the sensor nodes’ positions and orientations, as well as the source positions, are alternatingly estimated in an iterative process. Given one set of unknowns, i.e., either the source positions or the sensor nodes’ geometry, the other set of unknowns can be computed in closed-form. The proposed approach is computationally efficient and the first one, which employs both distance and directional information for geometry calibration in a common cost function. Since both distance and direction of arrival measurements suffer from outliers, e.g., caused by strong reflections of the sound waves on the surfaces of the room, we introduce measures to deemphasize or remove unreliable measurements. Additionally, we discuss modifications of our previously proposed deep neural network-based acoustic distance estimator, to account not only for omnidirectional sources but also for directional sources. Simulation results show good positioning accuracy and compare very favorably with alternative approaches from the literature.

Iterative Geometry Calibration from Distance Estimates for Wireless Acoustic Sensor Networks - Gburrek, Tobias; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (ICASSP 2021 - 2021 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

On Source-Microphone Distance Estimation Using Convolutional Recurrent Neural Networks - Gburrek, Tobias; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (Speech Communication; 14th ITG-Symposium)

Online Estimation of Sampling Rate Offsets in Wireless Acoustic Sensor Networks with Packet Loss - Chinaev, Aleksej; Enzner, Gerald; Gburrek, Tobias; Schmalenstroeer, Joerg (29th European Signal Processing Conference (EUSIPCO))

Seelsorge der Geschichte? Konfessionelle Geschichtspolitik im 17. Jahrhundert am Beispiel der Monumenta Paderbornensia Ferdinands von Fürstenberg - Moritz, Tilman (Katholische Konfessionalisierung in Paderborn? Religiöse Prozesse in der Frühen Neuzeit)

Forschungsperspektiven - Moritz, Tilman; Kopp, Stefan; Priesching, Nicole (Katholische Konfessionalisierung in Paderborn? Religiöse Prozesse in der Frühen Neuzeit)

Zum Paradigma der Konfessionalisierung - Moritz, Tilman; Kopp, Stefan; Priesching, Nicole (Katholische Konfessionalisierung in Paderborn? Religiöse Prozesse in der Frühen Neuzeit)

A. Seidler, I. Monok (Hgg.): Reformation und Bücher. Zentren der Ideen – Zentren der Buchproduktion. Wiesbaden 2020 - Moritz, Tilman (sehepunkte)

Das Commentariolum Ferdinands von Fürstenberg – eine lateinisch-deutsche Synopse - Moritz, Tilman (Katholische Konfessionalisierung in Paderborn? Religiöse Prozesse in der Frühen Neuzeit)

Katholische Konfessionalisierung in Paderborn? Religiöse Prozesse in der Frühen Neuzeit

Max Schulze vs. Joana Dahlhoff - Schulze, Max (Joana Dahlhoff: Recherche patiente)

Shared Leadership: Neue Studien für die Unternehmenspraxis - Krebs, Benjamin; Kabst, Rüdiger (PERSONALquartely)

HR-Manager als Intrapreneure - Wach, Bernhard; Krebs, Benjamin; Kabst, Rüdiger (HR-Trends 2021)

Contrastive Predictive Coding Supported Factorized Variational Autoencoder for Unsupervised Learning of Disentangled Speech Representations - Ebbers, Janek; Kuhlmann, Michael; Cord-Landwehr, Tobias; Haeb-Umbach, Reinhold (Proceedings of the IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))
In this work we address disentanglement of style and content in speech signals. We propose a fully convolutional variational autoencoder employing two encoders: a content encoder and a style encoder. To foster disentanglement, we propose adversarial contrastive predictive coding. This new disentanglement method does neither need parallel data nor any supervision. We show that the proposed technique is capable of separating speaker and content traits into the two different representations and show competitive speaker-content disentanglement performance compared to other unsupervised approaches. We further demonstrate an increased robustness of the content representation against a train-test mismatch compared to spectral features, when used for phone recognition.

Human Factors in Secure Software Development - Acar, Yasemin

A Large-Scale Interview Study on Information Security in and Attacks against Small and Medium-sized Enterprises - Huaman, Nicolas; von Skarczinski, Bennet; Stransky, Christian; Wermke, Dominik; Acar, Yasemin; Dreißigacker, Arne; Fahl, Sascha (30th USENIX Security Symposium, USENIX Security 2021, August 11-13, 2021)

Why Eve and Mallory Still Love Android: Revisiting TLS (In)Security in Android Applications - Oltrogge, Marten; Huaman, Nicolas; Amft, Sabrina; Acar, Yasemin; Backes, Michael; Fahl, Sascha (30th USENIX Security Symposium, USENIX Security 2021, August 11-13, 2021)

Passivität als Widerstand gegen die Macht der Verhältnisse? Melvilles Bartleby, the scrivener aus literaturwissenschaftlicher und ökonomischer Perspektive - Öhlschläger, Claudia; Schneider, Martin (Komparatistik heute)

Happy clappy heile Welt? Wie angesichts von Krisen und Katastrophen eine schöne Welt besungen werden kann - Neumann, Anna (Musik als Lebensmittel. Kulturwissenschaftlich-theologische Rationen für ein Jahr)

This is my Fight Song - Neumann, Anna; Katharina, Kammeyer; Vera, Uppenkamp (Musk als Lebensmittel)

Keller, Raabe, Fontane: ›nichts für den Durchschnittsleser‹. Miszellane Lektüren, ›imaginäre Leser‹ und Kanonisierungsprozesse in der Literaturkritik der zeitgenössischen Presse - Gretz, Daniela (Miszellanes Lesen. Interferenzen zwischen medialen Formaten, Romanstrukturen und Lektürepraktiken im 19. Jahrhundert)

Miszellanes Lesen. Interferenzen zwischen medialen Formaten, Romanstrukturen und Lektürepraktiken im 19. Jahrhundert

Mit Aufgaben im inklusiven Mathematikunterricht professionell umgehen - Erkenntnisse einer Interviewstudie mit Lehrpersonen der Sekundarstufe - Häsel-Weide, Uta; Seitz, Simone; Wallner, Melina; Wilke, Yannik; Heckmann, Lara (QfI - Qualifizierung für Inklusion. Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)

Conceptualiziation processes of 6th graders for rotational symmetry - Hattermann, Mathias; Häsel-Weide, Uta; Wallner, Melina (Proceedings of the 44th Conference of the International Group for the Psychology of Mathematics Education)

Zusammenhang zwischen familiären Lebenssituationen und Werteähnlichkeiten in der Eltern-Kind-Beziehung im Erwachsenenalter. - Hoellger, Christian; Sommer, Sabrina; Buhl, Heike M. (Zeitschrift für Soziologie der Erziehung und Sozialisation)

Bifurcation preserving discretisations of optimal control problems - Offen, Christian; Ober-Blöbaum, Sina
The first order optimality conditions of optimal control problems (OCPs) can be regarded as boundary value problems for Hamiltonian systems. Variational or symplectic discretisation methods are classically known for their excellent long term behaviour. As boundary value problems are posed on intervals of fixed, moderate length, it is not immediately clear whether methods can profit from structure preservation in this context. When parameters are present, solutions can undergo bifurcations, for instance, two solutions can merge and annihilate one another as parameters are varied. We will show that generic bifurcations of an OCP are preserved under discretisation when the OCP is either directly discretised to a discrete OCP (direct method) or translated into a Hamiltonian boundary value problem using first order necessary conditions of optimality which is then solved using a symplectic integrator (indirect method). Moreover, certain bifurcations break when a non-symplectic scheme is used. The general phenomenon is illustrated on the example of a cut locus of an ellipsoid.
Keywords: optimal control; catastrophe theory; bifurcations; variational methods; symplectic integrators

Learning ODE Models with Qualitative Structure Using Gaussian Processes - Ridderbusch, Steffen; Offen, Christian; Ober-Blöbaum, Sina; Goulart, Paul (2021 60th IEEE Conference on Decision and Control (CDC))

Multi-objective minimum time optimal control for low-thrust trajectory design - Vertovec, Nikolaus; Ober-Blöbaum, Sina; Margellos, Kostas
We propose a reachability approach for infinite and finite horizon multi-objective optimization problems for low-thrust spacecraft trajectory design. The main advantage of the proposed method is that the Pareto front can be efficiently constructed from the zero level set of the solution to a Hamilton-Jacobi-Bellman equation. We demonstrate the proposed method by applying it to a low-thrust spacecraft trajectory design problem. By deriving the analytic expression for the Hamiltonian and the optimal control policy, we are able to efficiently compute the backward reachable set and reconstruct the optimal trajectories. Furthermore, we show that any reconstructed trajectory will be guaranteed to be weakly Pareto optimal. The proposed method can be used as a benchmark for future research of applying reachability analysis to low-thrust spacecraft trajectory design.

Fractional Damping Through Restricted Calculus of Variations - Jiménez, F.; Ober-Blöbaum, Sina (Nichtlineare Sci 31)

Der steinige Weg vom Wissen zum Können: Zum schwierigen Verhältnis von Theorie und Praxis bei der Betreuung zukünftiger Geschichtslehrkräfte in Langzeitpraktika - Hartung, Olaf; Krebs, Alexandra; Fastlabend-Vargas, Daniel; Meyer-Hamme, Johannes (Theorie und Praxis in der Lehrerbildung.Verhältnisbestimmungen aus der Perspektive von Fachdidaktiken)

„Da öffnet er ihnen das Verständnis, sodass sie die Schriften verstanden“ (Lk 24,45) - Breuer, Saskia Rebecca (Der Dom. Katholisches Magazin im Erzbistum Paderborn)

The Rise of Interactional Multimodality in Human-Computer Interaction - Klowait, Nils; Ерофеева, Мария Александровна (The monitoring of public opinion economic&social changes)
The field of human-computer interaction (HCI) investigates the intersection between the design of devices and users. From an early focus on interaction modeling based on psychological experiments, the field has since experienced a shift towards the study of how actual humans interact with autonomous devices. The field became conductive to ethnographic, observational and videographic studies of human-device interaction. Conversation-analytic HCI became possible. That said, this new wave of researchers was never truly able to dethrone the psychological common sense of the field. With recent developments in both the technical-sensorial capabilities and outward actuational range of embodied virtual agents, the field of HCI has once again returned to the question of the sequential unfolding of the interaction between users and intelligent agents, and the multimodal interactional repertoire that is deployed throughout. This review will highlight the situational orientation of high-impact research in the field, and relate it to the cotemporaneous development of ethnomethodological and conversation analytic frameworks. Acknowledgments. The article was prepared in the framework of a research grant funded by the Ministry of Science and Higher Education of the Russian Federation (grant ID: 075-15-2020-908). The article was prepared in cooperation with the Sber (ex. – Sberbank’s) Gamification Lab.
Keywords: Economics; Econometrics and Finance (miscellaneous); Sociology and Political Science

Home-Office. Kulturelle Formationen häuslicher Arbeit - Miggelbrink, Monique; Bartz, Christina (Selbstbehältnisse. Orte und Gegenstände der Aufbewahrung von Subjektivität)

Forschungsfelder für Künstliche Intelligenz in der strategischen Produktplanung - Ködding, Patrick; Dumitrescu, Roman (Digitalisisierung souverän gestalten)

Selective area growth of cubic gallium nitride on silicon (001) and 3C-silicon carbide (001) - Meier, F.; Protte, M.; Baron, E.; Feneberg, M.; Goldhahn, R.; Reuter, Dirk; As, Donat Josef (AIP Advances)

“Seeing Is Believing”—In-Depth Analysis by Co-Imaging of Periodically-Poled X-Cut Lithium Niobate Thin Films - Reitzig, Sven; Rüsing, Michael; Zhao, Jie; Kirbus, Benjamin; Mookherjea, Shayan; Eng, Lukas M. (Crystals)
Nonlinear and quantum optical devices based on periodically-poled thin film lithium niobate (PP-TFLN) have gained considerable interest lately, due to their significantly improved performance as compared to their bulk counterparts. Nevertheless, performance parameters such as conversion efficiency, minimum pump power, and spectral bandwidth strongly depend on the quality of the domain structure in these PP-TFLN samples, e.g., their homogeneity and duty cycle, as well as on the overlap and penetration depth of domains with the waveguide mode. Hence, in order to propose improved fabrication protocols, a profound quality control of domain structures is needed that allows quantifying and thoroughly analyzing these parameters. In this paper, we propose to combine a set of nanometer-to-micrometer-scale imaging techniques, i.e., piezoresponse force microscopy (PFM), second-harmonic generation (SHG), and Raman spectroscopy (RS), to access the relevant and crucial sample properties through cross-correlating these methods. Based on our findings, we designate SHG to be the best-suited standard imaging technique for this purpose, in particular when investigating the domain poling process in x-cut TFLNs. While PFM is excellently recommended for near-surface high-resolution imaging, RS provides thorough insights into stress and/or defect distributions, as associated with these domain structures. In this context, our work here indicates unexpectedly large signs for internal fields occurring in x-cut PP-TFLNs that are substantially larger as compared to previous observations in bulk LN.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering